High Affinity Recognition of a Selected Amino Acid Epitope within a Protein by Cucurbit[8]uril Complexation. (13th October 2016) - Sonzini, Silvia; Marcozzi, Alessio; Gubeli, Raphael J.; van der Walle, Christopher F.; Ravn, Peter; Herrmann, Andreas; Scherman, Oren A.
Abstract: Supramolecular interactions between the host cucurbit[8]uril (CB[8]) and amino acids have been widely interrogated, but recognition of specific motifs within a protein domain have never been reported. A phage display approach was herein used to select motifs with the highest binding affinity for the heteroternary complex with methyl viologen and CB[8] (MV⋅CB[8]) within a vast pool of cyclic peptide sequences. From the selected motifs, an epitope consisting of three amino acid was extrapolated and incorporated into a solvent‐exposed loop of a protein domain; the protein exhibited micromolar binding affinity for the MV⋅CB[8] complex, matching that of the cyclic peptide. By achieving selective CB[8]‐mediated conjugation of a small molecule to a recombinant protein scaffold we pave the way to biomedical applications of this simple ternary system.